Persepsi Pemilih Penyandang Disabilitas terhadap Peran Badan Ad Hoc KPU dalam Pemilu 2019 di Kabupaten Muna - Delawahyuni, Delawahyuni (Journal of Politics and Democracy, 2024)
This study aims to describe the perceptions of voters with disabilities regarding the performance of the KPU’s ad hoc body during the 2019 General Election in Muna Regency. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and document review. The data were analyzed qualitatively through stages of fact identification, verification, validation, interpretation, and in-depth analysis. The findings indicate that the KPU’s ad hoc body in Muna Regency has not yet fully carried out its duties effectively. This is reflected in the limited access of voters with disabilities to election outreach activities, largely due to the lack of special attention given to their needs. Political education and socialization efforts have not been evenly distributed, suggesting that the ad hoc body still lacks a comprehensive understanding of its institutional responsibilities. Voters with disabilities expect the KPU to improve its performance, particularly by providing accessible facilities and infrastructure that would reduce the risk of abstention among disabled voters.